(untitled) (Bangladesh Pharmaceutical Journal, 2015)
Irrational prescribing of drugs is a major health concern in developing countries like Bangladesh. A study was therefore undertaken in a hospital, situated in Rajshahi region of Bangladesh, to find the prescribing pattern and to detect the prescription errors to the admitted patients. Prescriptions of 200 patients were collected from various departments of the hospital over a period of three months. Prescription pattern was analyzed using general indicators suggested by WHO and prescribing errors were determined by comparing the prescribed drugs with national standard treatment guidelines, textbooks and authentic online resources. The average number of drugs per prescription was found to be 4.89 and 76.5% prescriptions contained complex regimen. In this study, we found no prescription with generic name. The percentage of prescription with antibiotics was 78% that was 15.95% of total drugs. The injectable preparations used were 17.18% of total 978 drugs. About 769 (3.85 per prescription) prescription errors were identified from 978 prescribed drugs. The name of 35 prescribed drugs was not clear due to illegible hand writing. The dose strength was missing for 279 drugs and 31 drugs had improper abbreviation. The study also identified 409 drug interactions. About 6.5% prescription orders were identified for the patients with kidney and urinary problems and there was no dose adjustment. Frequency of occurrence of prescription errors found during the study can be rated high. The prescription pattern and the prescription errors have indicated the need to establish proper system of recording and analyzing therapy before writing a prescription in order to promote rational drug therapy. Bangladesh Pharmaceutical Journal 18(1): 20-24, 2015